Statické řešení bytového domu - Svobodová, Barbora (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Předmětem diplomové práce je statické řešení vybraných železobetonových prvků bytového domu. Konkrétně je řešena železobetonová stropní deska nadzemního podlaží, lokálně podepřená deska podzemních garáží, nejvíce namáhaný sloup, schodiště, stěna jádra, vnější stěna a založení objektu na pilotách. Výpočet vnitřních sil byl proveden v programu Axis VM 12. Návrh založení byl proveden v programu Geo 5. Součástí práce je také výkresová dokumentace vybraných prvků.

The master's thesis deals with static analysis of selected reinforced concrete elements of an apartment building. Specifically solved are the reinforced concrete slab of above-ground floor, point-supported slab of underground garage, the most exposed column, staircase, load-bearing wall of shear core, external load-bearing wall and building foundation on piles. Load effects were calculated using the Axis VM 12 software. Design of foundation was solved in the Geo 5 software. The thesis includes shape drawing documentation of selected elements.
Statical design of residential house
Keywords: Vnitřní síly; návrh výztuže; železobetonová deska; sloup; stěna; vrtaná pilota; schodiště; zatížení; sedání základu; založení.; Internal forces; design of reinforcement; reinforced concrete slab; column; load-bearing wall; bored pile; staircase; load; settlement of foundation; foundation.